An Overview of the Application of Nanoscience in Cancer Diagnosis and Treatment - Sheikhi, Salman; Asghari Hosori, Negar; Yari, Saeed (Asian Pacific Journal of Environment and Cancer, 2023)
Cancer is one of the most common causes of death. One of the most important problems in cancer treatment is the side effects of drugs and treatments. The limiting factor in cancer treatment is the lack of selectivity of drugs against cancer cells. Today, nanotechnology has been able to help in the diagnosis and treatment of this disease because most biological processes such as the creation of cancer occur in nano dimensions, therefore, in order to reduce side effects and improve existing drugs, various drug delivery systems based on nanotechnology have been developed. Cancer researchers use the ability of nanotechnology to evaluate cells and achieve the following goals: 1- Simulating the reaction of cells with protein and nucleic acids at the molecular level, and then obtaining a proper knowledge of cell behavior. 2- Studying the structure and function of intracellular proteins and research in the field of proteomics. 3- Initial determination of cancer. This article is written based on reviews of various articles in reputable journals and books related to the use of nanotechnology in cancer treatment. The selection of sources is based on suitability to the topic, year of research, non-repetition and comprehensiveness of the content. The effective treatment of cancer with the least side effects is considered one of the challenges of medical and pharmaceutical sciences, and the introduction of nanotechnology into therapeutic fields promises the production of a new group of anti-cancer drugs that provide diagnostic and therapeutic capabilities simultaneously. These structures have a special place in cancer treatment as drug carriers and optically and thermally active substance